Opuść nawiasy i wykonaj redukcję wyrazów podobnych:

a) (2x – 3) + (3x – 4) – (6x + 1) =

b) (x2 – 3x -5) + (2x2 + 4x + 6) + (-x2 – x +2) =

c) (-y2 – 5y) – (3y2 + 2y – 4) – (7y2 + 4) =

d) (2,7x – 3,2y + 12,5) – (3,8x – 2,2y + 3,6) + (4,5x + 3) =

e) (x3 + 2y2 – 1,5) – (3x3 – 4y2 – 5) + (2x3 – 5y2 – 6,5) =

f) -(3x + 2) + (4y – 3x + 4) - 22 =

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T18:56:26+01:00
A) (2x – 3) + (3x – 4) – (6x + 1) = 2x-3+3x-4-6x-1=-x-8

b) (x2 – 3x -5) + (2x2 + 4x + 6) + (-x2 – x +2) =
x2-3x-5+2x2+4x+6-x2-x+2=-3x-5+2x2+4x+6=9x+1+2x2

c) (-y2 – 5y) – (3y2 + 2y – 4) – (7y2 + 4) =-y2-5y-3y2-2y+4-7y2+4=
-9y2-7y+8

d) (2,7x – 3,2y + 12,5) – (3,8x – 2,2y + 3,6) + (4,5x + 3) =
2,7x-3,2y+12,5-3,8x+2,2y-3,6+4,5x+3=3,4x-y+19,1

e) (x3 + 2y2 – 1,5) – (3x3 – 4y2 – 5) + (2x3 – 5y2 – 6,5) =x3+2y2-1,5-3x3+4y2+5+2x3-5y2-6,5=y2-3

f) -(3x + 2) + (4y – 3x + 4) - 22 =-3x-2+4y-3x+4-22=
-6x+4y-20
2010-01-27T19:01:57+01:00
A) (2x – 3) + (3x – 4) – (6x + 1) =2x-3+3x-4-6x-1=-x-8

b) (x2 – 3x -5) + (2x2 + 4x + 6) + (-x2 – x +2) =
=2x-3x-5+4x+4x+6+(-2x)-x+2 = 6x+3

c) (-y2 – 5y) – (3y2 + 2y – 4) – (7y2 + 4) =
=-2y-5y-6y-2y+4-14y-4 = -19y +0= -19y

d) (2,7x – 3,2y + 12,5) – (3,8x – 2,2y + 3,6) + (4,5x + 3) =
=2,7x-3,2y+12,5-3,8x+2,2y-3,6+4,5x+3= 3,4x-y+15,5

e) (x3 + 2y2 – 1,5) – (3x3 – 4y2 – 5) + (2x3 – 5y2 – 6,5) =
3x+4y-1,5-9x+8y+5+6x-10y-6,5=0+2y-3

f) -(3x + 2) + (4y – 3x + 4) - 22 =
=-3x-2+4y-3x+4-22=-6x+4y-20